2018
DOI: 10.1038/s41467-018-06886-8
|View full text |Cite
|
Sign up to set email alerts
|

Inherent potential of steelmaking to contribute to decarbonisation targets via industrial carbon capture and storage

Abstract: Accounting for ~8% of annual global CO2 emissions, the iron and steel industry is expected to undertake the largest contribution to industrial decarbonisation. Despite the launch of several national and regional programmes for low-carbon steelmaking, the techno-economically feasible options are still lacking. Here, based on the carbon capture and storage (CCS) strategy, we propose a new decarbonisation concept which exploits the inherent potential of the iron and steel industry through calcium-looping lime pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 35 publications
0
69
0
Order By: Relevance
“…Here, the CaO from CaL can be used in DAC, or if DAC is carried out with a lime-based sorbent, then the spent lime can be fed back into the cement industry. Recently, it has also been demonstrated that lime can be very efficiently used in the steel industry for decarbonization as well, using a variant of the CaL option (Tian et al 2018). The basic philosophy of this work is that limestone and lime-based materials are ubiquitous, cheap, nontoxic and are compatible with two of the most important industrial sources of anthropogenic CO 2 (namely cement and steel), and a lime-based process, if it can be made to perform at a comparable level to DAC processes using sodium or potassium hydroxide, is inherently preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the CaO from CaL can be used in DAC, or if DAC is carried out with a lime-based sorbent, then the spent lime can be fed back into the cement industry. Recently, it has also been demonstrated that lime can be very efficiently used in the steel industry for decarbonization as well, using a variant of the CaL option (Tian et al 2018). The basic philosophy of this work is that limestone and lime-based materials are ubiquitous, cheap, nontoxic and are compatible with two of the most important industrial sources of anthropogenic CO 2 (namely cement and steel), and a lime-based process, if it can be made to perform at a comparable level to DAC processes using sodium or potassium hydroxide, is inherently preferable.…”
Section: Introductionmentioning
confidence: 99%
“…Effective decarbonisation of the industrial sector is a key wedge for meeting low climate warming targets 1 , 2 . The iron and steel industry is a particularly energy- and emission-intensive sector that accounts for ~8% of annual global anthropogenic CO 2 emissions, >2800 Mt CO 2 per year 3 – 5 . Two recent emissions scenarios to limit warming below 2 °C 4 , 5 proposed that the CO 2 budget of iron and steel emissions should be capped at 50 Gt between now and 2050.…”
Section: Introductionmentioning
confidence: 99%
“…The iron and steel industry is a particularly energy- and emission-intensive sector that accounts for ~8% of annual global anthropogenic CO 2 emissions, >2800 Mt CO 2 per year 3 – 5 . Two recent emissions scenarios to limit warming below 2 °C 4 , 5 proposed that the CO 2 budget of iron and steel emissions should be capped at 50 Gt between now and 2050. Meeting this budget is challenged by the persistently growing steel demand, which is expected to rise from 1.82 Gt-steel in 2020 to 2.55 Gt-steel in 2050 5 , 6 , driven by urbanisation and industrialisation in non-OECD countries 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fossil fuels account for 81% of the total energy consumption [5]. Second, some carbonbased resources are essential for industries, such as steel making, where high-temperature heat is required [6][7][8]. Copious amounts of by-product gas are generated in each unit process in the steel industry, which is the core industry of our society [9].…”
Section: Introductionmentioning
confidence: 99%